2021
DOI: 10.1101/2021.07.13.21260465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutational landscape of high-grade B-cell lymphoma with MYC-, BCL2 and/or BCL6 rearrangements characterized by whole-exome sequencing

Abstract: High-grade B-cell lymphoma accompanied with MYC and BCL2 and/or BCL6 rearrangements (HGBL-DH/TH) poses a cytogenetically-defined provisional entity among aggressive B-cell lymphomas that is traditionally associated with unfavorable prognosis. To better understand the mutational and molecular landscape of HGBL-DH/TH we here performed whole-exome sequencing and deep panel next-generation-sequencing (NGS) of 47 clinically annotated cases. Oncogenic drivers, mutational signatures and perturbed pathways were compa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Beyond a significant congruency with the C3/EZB DLBCL cluster in BCL2 rearranged cases on an exome-wide level, they observed an enrichment of the SBS6 mutation signature in BCL6 rearranged cases. SBS6 is associated with defective DNA mismatch repair and is found in microsatellite unstable tumors [9]. Differential gene set enrichment and subsequent network propagation analysis according to cytogenetically defined subgroups revealed an impairment of TP53 and MYC pathway signaling in BCL2 rearranged cases, whereas BCL6 rearranged cases lacked this enrichment, but instead exhibited showed impairment of E2F targets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Beyond a significant congruency with the C3/EZB DLBCL cluster in BCL2 rearranged cases on an exome-wide level, they observed an enrichment of the SBS6 mutation signature in BCL6 rearranged cases. SBS6 is associated with defective DNA mismatch repair and is found in microsatellite unstable tumors [9]. Differential gene set enrichment and subsequent network propagation analysis according to cytogenetically defined subgroups revealed an impairment of TP53 and MYC pathway signaling in BCL2 rearranged cases, whereas BCL6 rearranged cases lacked this enrichment, but instead exhibited showed impairment of E2F targets.…”
Section: Discussionmentioning
confidence: 97%
“…Differential gene set enrichment and subsequent network propagation analysis according to cytogenetically defined subgroups revealed an impairment of TP53 and MYC pathway signaling in BCL2 rearranged cases, whereas BCL6 rearranged cases lacked this enrichment, but instead exhibited showed impairment of E2F targets. Oncogenic drivers, mutational signatures and perturbed pathways were compared with data from follicular lymphoma (FL), diffuse large-B-cell lymphoma (DLBCL) and Burkitt lymphoma (BL) [9]. C-MYC/BCL2 HGBL DH usually attended to GCB lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…KMT2D , SOCS1 , and BCL2 were frequently mutated in DHL/THL but not in SHL. Previously reported NGS data of DHL/THL showed CREBBP , BCL2 , KMT2D , MYC , EZH2 , IGLL5 , FOXO1 , SOCS1 and SI are frequently mutated genes [ 16 , 17 , 18 ]. Evrard et al stated that for DHL/THL, the most frequently mutated genes were like those reported in DLBCL NOS, especially in GCB-DLBCL, but the percentage of DHL/THL with mutations on eight genes ( CREBBP , BCL2 , KMT2D , MYC , EZH2 , IGLL5 , FOXO1 and SOCS1 ) was significantly higher than that of reported DLBCL, NOS [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aukema SM et al demonstrated that comparative copy number alteration (CNA) of DHL/THL had higher frequencies of gains at chromosome loci 8q and 12q compared with SHL (9). Next-generation target sequencing (NGS) demonstrated that the mutational profile of DHL/THL differed from that of DLBCL, NOS [ 16 , 17 , 18 ]. Gene expression profile analyses of DHL/THL revealed that DHL with BCL2 -R (DHL- BCL2 ) and THL had germinal center B-cell-like (GCB) profiles [ 6 , 9 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In BL, we already assessed the prognostic role of MYC insertions or concomitant BCL2 and BCL6 mutations [46, 51]. In B-ALL/LBL and HGBL with MYC and BCL2 and/or BCL6 rearrangements, NGS sequencing has shown recurrent variants of genes coding for transcription factors (MYC, FOXO1), epigenetic modulators (KMT2D, EZH2, and CREBBP), and antiapoptotic proteins (BCL2) [51, 52]. In PTCL, NGS profiling matches with PCR-based T-cell clonality assessment [53].…”
Section: Ancillary Techniquesmentioning
confidence: 99%